The Comparison of Stock Price Before and After Pandemic to Identify The Health of Sector Company - Retinda Liandya Gita; Endang Chumaidiyah; Rita Zulbetti (International Journal of Innovation in Enterprise System, 2022)
At the beginning of the Covid-19 outbreak in Indonesia, almost all activities in this country were disrupted and economic activity was no exception. Indonesia's current economic growth is down 2.07% in 2020 due to the Covid-19 pandemic which has caused it to be reduced to a low and middle-income country. Based on the gross domestic product (GDP), most sectors of the Indonesian economy experienced a decline in growth in 2020. Only 5 economic sectors showed positive growth. The sector with the largest positive growth was the health services sector and social activities, which amounted to 11.60%. This growth affects the stock price of health sector companies. Grounded on the IDX Industry category (IDXHEALTH) from 2018-2022, there was an increase of 41.28%. The Health Sector which continues to grow is driven by the payment of Covid- 19 incentives. This study was conducted to identify the Difference in Stock prices of Health Sector Companies before and after Covid- 19 with the supposition that the Covid- 19 pandemic occurred in March 2020 by observing stock price fluctuations two years before and after the Covid- 19 Pandemic. Based on the Paired Sample T-test, the stock prices of 3 companies from 6 companies have significant differences in the specified sample period, namely DVLA, PRDA, and MERK companies where the stock prices of DVLA and PRDA have increased. In addition, PRDA's stock price has the largest stock price among other health sector companies, meaning that PRDA companies have good performance.